PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI PT LUHAI INDUSTRIAL - Ahmad Ropiudin; Euis Ajizah; Pipin Suryanisari (Universitas La Tansa Mashiro, 2025)
The aim of this research is to analyze the influence of work motivation and job satisfaction on the performance of PT employees. Luhai Industrial. In This Research, 344 Employees Of Pt. Industrial Luhai as a population. And the sample used was 77 employees, calculated based on the Slovin formula. The data collection method uses a survey method, with the research instrument in the form of a questionnaire. This research uses a quantitative method with a saturated sampling technique. This analysis uses multiple linear regression analysis assisted by SPSS Version 20 software. This research proves that work motivation has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance.